EMOÇÕES NA EDUCAÇÃO INFANTIL: REFLEXÕES ACERCA DA PRÁTICA PEDAGÓGICA DE PROFESSORAS EM UMA ESCOLA MUNICIPAL DE SANTA MARIA, RS - Santana, Fernanda Inocente (2020)
The research started as an investigative focus the emotions in the context of Early Childhood Education, having as an element to be analyzed the pedagogical practice of the teacher in the classroom in the face of the emotional manifestations of the children. In this direction, the present research project contemplated as a research problem "How does the teacher of Early Childhood Education in his pedagogical practice work the emotions of children in the classroom?". The study was characterized as empirical and qualitative, in which the general objective of which the teacher of Early Childhood Education in his pedagogical practice works the emotions of children in the classroom and, the specific objectives, started, first, from an exposition of the historical context and the importance of emotions in Early Childhood Education, the verification of the importance conferred by teachers of Early Childhood Education at work with the emotions presented by the children in the classroom, the difficulties were investigated and challenges in pedagogical practice. Early Childhood Education was chosen because it is an area in which the contacts with the emotions of children in their daily lives go beyond the classroom, which is one of the first contexts of socialization, development and learning of the child, a fact that affirms the need to know which methods and actions are undertaken by the educator in the face of the students' emotions. To achieve its objectives, the methodology adopted was the semi-structured interview, and 06 (six) teachers of Early Childhood Education were interviewed, namely: 02 (two) teachers of the maternal (age group of the students is 3 years), 02 (two) teachers of the Pre-A (age group of the students is 4 years) and 02 (two) teachers of the Pre-B (age group 5 years). The results obtained allowed a greater perception about the importance of the studies of emotions in the performance of the teacher or acts in Early Childhood Education. In addition, he presented that the greatest difficulties are under the aspect of connection between family/school, teacher/management, and as a challenge to overcome, it was pointed out that there is a need to search for new methodologies, given the need to understand the child as a social, active and participative subject. Finally, it is pointed out that emotions alone have an intrinsic character to the human being, in which being a work contributes to the greater physical and cognitive development of each one.